Cyclic Voltammetric Study of Protonation Reactions of Some Dinitroaromatics in Propylene Carbonate - Hanif, Farzana; Yasmeen, Ghazala; Manzoor, Suryyia; Sohail, Muhammad; Amir, Muhammad (Asian Journal of Chemistry, 2015)
Cyclic voltammetric technique is used to study the protonation of anion radicals of 1,2-dinitrobenzene and 1,3-dinitrobenzene in propylene carbonate in the temperature range 5, 15, 25 and 35 °C. Glassy carbon electrode and hanging mercury drop electrode are used as working electrodes. Benzoic acid and salicylic acid are used as protonating agents. Homogeneous rate constant is calculated by using Nicholson and Shain equation. The position of nucleophilic attack in dinitrobenzenes has been investigated by calculation of charge densities using molecular orbital methods. The heterogeneous rate constant ks,h for the first reduction process in dinitrobenzenes is determined by digital simulation of the cyclic voltammograms.